VS BRIKET ARANG (Studi Kelayakan Pendirian Usaha Briket Arang Kelapa Di Kota Palembang) - Vincent, Vincent; Megawati, Megawati (Universitas Multi Data Palembang, 2023)
VS Charcoal Briquettes is a business engaged in trading that sells charcoalbriquettes from coconut shells, which are planned to be marketed to restaurants and UMKM thatuse charcoal as a cooking medium for their products, VS Charcoal Briquettes are trying tointroduce this coconut charcoal briquettes to be used in restaurants , UMKM and evensupermarkets in the city of Palembang, this is done not without reason, judging from theadvantages of this coconut charcoal briquette, it is very much compared to the use of ordinarycharcoal. Other things that burn easily or quickly burn, coconut shell charcoal briquettes have along usability because they don't run out quickly when burned, in the process of burning charcoalbriquettes do not have flying powder and also the smoke produced by charcoal briquettes is not asmuch as ordinary charcoal. reduce smoke pollution in the city of Palembang, the use of briquetteset coconut shell charcoal is also considered safer than ordinary charcoal, because it has a slowburning power.